Distance and direction-based location aided multi-hop routing protocol for vehicular ad-hoc networks. (2016) - Pandey, Kavita; Raina, Saurabh Kumar; Raw, Ram Shringar
Vehicular ad-hoc network (VANET) is an important technology for future development of intelligent transportation systems. Due to the highly-dynamic nature of vehicular nodes, network topology changes very frequently which complicate the routing of data packets. A number of routing protocols have been developed by various researchers. Hop count is a key parameter in evaluating the performance of a routing protocol. Number of hops required in directional routing protocols is more in comparison to other routing protocols. For a city vehicular traffic scenario we propose an improved direction-based location aided routing (D-LAR) protocol that we call distance and direction-based location aided routing (DD-LAR) protocol. A mathematical model for DD-LAR protocol has been developed to examine its performance on path duration and hop count metric. Simulations have been done in MATLAB and from the results, it can be seen that DD-LAR routing protocol shows significant performance improvement over D-LAR and LAR in terms of reducing the hop count and maximising the path duration.